Parental age does not influence offspring telomeres during early life in common gulls (Larus canus). Issue 23 (12th April 2021) - Sepp, Tuul; Meitern, Richard; Heidinger, Britt; Noreikiene, Kristina; Rattiste, Kalev; Hõrak, Peeter; Saks, Lauri; Kittilson, Jeffrey; Urvik, Janek; Giraudeau, Mathieu
Abstract: Parental age can affect offspring telomere length through heritable and epigenetic‐like effects, but at what stage during development these effects are established is not well known. To address this, we conducted a cross‐fostering experiment in common gulls ( Larus canus ) that enabled us distinguish between pre‐ and post‐natal parental age effects on offspring telomere length. Whole clutches were exchanged after clutch completion within and between parental age classes (young and old) and blood samples were collected from chicks at hatching and during the fastest growth phase (11 days later) to measure telomeres. Neither the ages of the natal nor the foster parents predicted the telomere length or the change in telomere lengths of their chicks. Telomere length (TL) was repeatable within chicks, but increased across development (repeatability = 0.55, intraclass correlation coefficient within sampling events 0.934). Telomere length and the change in telomere length were not predicted by post‐natal growth rate. Taken together, these findings suggest that in common gulls, telomere length during early life is not influenced by parental age or growth rate, which may indicate that protective mechanisms buffer telomeres from external conditions during development in this relatively long‐lived species.